2019
DOI: 10.1051/0004-6361/201935140
|View full text |Cite
|
Sign up to set email alerts
|

Is spectral width a reliable measure of GRB emission physics?

Abstract: The spectral width and sharpness of unfolded, observed GRB spectra have been presented as a new tool to infer physical properties about GRB emission via spectral fitting of empirical models. Following the tradition of the 'line-of-death', the spectral width has been used to rule out synchrotron emission in a majority of GRBs. This claim is investigated via examination of both cataloged GRB spectra as well as reanalyzed spectra leading to the introduction of another empirical characterization of the spectra: th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The data of POLAR do not allow to determine the nature of the PA evolution for the two GRBs for which hints of it were found. The data are compatible with both random variations as well as a single 90 • change [104]. Finer time binning or higher statistics within the time bins are required to fully resolve this.…”
Section: Time-resolved Measurementsmentioning
confidence: 68%
See 2 more Smart Citations
“…The data of POLAR do not allow to determine the nature of the PA evolution for the two GRBs for which hints of it were found. The data are compatible with both random variations as well as a single 90 • change [104]. Finer time binning or higher statistics within the time bins are required to fully resolve this.…”
Section: Time-resolved Measurementsmentioning
confidence: 68%
“…This may become a problem in instances where such models are unable to capture the intrinsic complexity of the underlying data. Therefore, an arguably better approach is to directly fit physical models to the raw data to derive spectral parameters and remove any bias [103][104][105][106]. Such an approach has led to alleviating some of the issues encountered by the optically thin synchrotron model, where it was shown that direct spectral fits (in count space rather than energy space) with synchrotron emission from cooling power-law electrons can explain the low-energy spectral slopes as well as the spectral width of the peak [107].…”
Section: Optically-thin Synchrotron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous optical observations of the prompt γ-ray emission [45,61,66] provided interesting constraints on the broad-band spectral shape, the Lorentz factor, or the emission geometry. Detailed studies have been performed also on the shape of the prompt emission spectra, both on the sharpness of the peaks [176] as well as the conclusive answers provided by spectral fits with physical models [12,24,28,175] rather than empirical functions (like band, or cut-off power laws). Combined GBM and POLAR measurements of GRB 170111A provided further support for a synchrotron origin by revealing a smooth polarisation angle swing in concert with a declining peak energy [27].…”
Section: Glast/fermimentioning
confidence: 99%
“…In addition, the authors did not attempt to fit this theoretical model to the data, which might introduce instrumental biases in the comparison with the Band fit results. Direct fits of the synchrotron emission model to GRB prompt spectra have been performed by Zhang et al (2016) and Burgess (2019), who showed that the line-of-death and spectralsharpness issues are likely artefacts due to the use of the Band function (see also Ronchi et al 2020). Fitting the spectra with simpler versions of the synchrotron emission model or with empirical functions featuring a low-energy spectral break, especially on a broad energy range extending down to the X-ray and/or optical domain, appears able to reconcile the observations with the synchrotron theory as well, showing the expected transition from fast to slow cooling (Oganesyan et al 2017(Oganesyan et al , 2018(Oganesyan et al , 2019Ravasio et al 2018Ravasio et al , 2019.…”
Section: Introductionmentioning
confidence: 99%